Forest structures and carbon stocks of community forests with different forest management in Maha Sarakham Province, Thailand - WANNACHAI WANNASINGHA; BHUVADOL GOMONTEAN; YANNAWUT UTTARUK (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wannasingha W, Gomontean B, Uttaruk Y. 2023. Forest structures and carbon stocks of community forests with different forest management in Maha Sarakham Province, Thailand. Biodiversitas 24: 799-809. Forest management comprises strategies and practices to regulate human activities and the utilization of forest products. Management and regulations have various effects on forest structure, tree diversity and carbon accumulation. This study was conducted in three community forests with different levels of rule regulations and managed duration in the northeast of Thailand. Thirty of 20×20 m plots were placed for recording all trees with diameter at breast height (dbh) ?4.5 cm and >1.3 m height. One hundred and fifty plots of soil samples at 0-25 cm and 25-50 cm depths were also collected for organic carbon analysis. Forest carbon stocks were calculated from the sum of carbon in aboveground biomass (AGB) and soil organic carbon (SOC). The results showed that tree density, basal area, Shannon diversity index and evenness index of the best practices (BP) plots were higher than the plots in which moderate (MP) and slight practices (SP) were applied. Tree heights of the BP and MP forests were higher than the SP forest. The L-shape of dbh class distribution in all community forests means they were secondary forests; tree density was highest in the small dbh class and declined in the bigger size class. The bigger dbh class tree showed higher aboveground carbon (AGC) despite the lower tree density in all community forests. Most of the BP forest plots had the highest carbon stock (93.89, 80.52 and 54.96 Mg C ha-1) and CO2 absorption (344.25, 295.23 and 201.53 Mg CO2equiv.) compared with the others. Our results demonstrate the importance of forest management in affecting forest structures, carbon sequestration and carbon dioxide absorption from the atmosphere to reduce and mitigate climate change.